2020
DOI: 10.1002/ajmg.c.31851
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype–genotype analysis of 242 individuals with RASopathies: 18‐year experience of a tertiary center in Brazil

Abstract: We report the clinical and molecular data of a large cohort comprising 242 individuals with RASopathies, from a single Tertiary Center in Brazil, the largest study from Latin America. Noonan syndrome represented 76% of the subjects, with heterozygous variants in nine different genes, mainly PTPN11, SOS1, RAF1, LZTR1, and RIT1, detected by Sanger and next-generation sequencing. The latter was applied to 126 individuals, with a positive yield of 63% in genes of the RAS/MAPK cascade. We present evidence that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 58 publications
1
18
1
Order By: Relevance
“…The most prevalent mutation in European and North American populations, c.922A > G (p.Asn308Asp), was not found in this Brazilian study. A more recent Brazilian cohort with 242 individuals with RASopathies, of which 185 had a NS diagnosis, showed that PTPN11 p.Asn308Asp variant as the most prevalent in the cohort (21.4%) (Bertola et al, 2020). Rodríguez et al (2013) performed a molecular characterization of Chilean patients with clinical NS diagnosis and identified PTPN11 pathogenic variants in four out of 18 patients, but none with p.Asn308Asp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prevalent mutation in European and North American populations, c.922A > G (p.Asn308Asp), was not found in this Brazilian study. A more recent Brazilian cohort with 242 individuals with RASopathies, of which 185 had a NS diagnosis, showed that PTPN11 p.Asn308Asp variant as the most prevalent in the cohort (21.4%) (Bertola et al, 2020). Rodríguez et al (2013) performed a molecular characterization of Chilean patients with clinical NS diagnosis and identified PTPN11 pathogenic variants in four out of 18 patients, but none with p.Asn308Asp.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and molecular characterization of Noonan syndrome patients tends to be similar between patients of different ethnic backgrounds (Kruszka et al, 2017). Few studies have aimed to examine these features in the Latin American population (Bertola et al, 2006; Chinton, Huckstadt, Moresco, Gravina, & Obregon, 2019; Rodríguez, Unanue, Hernández, Heath, & Cassorla, 2013; Bertola et al, 2020). However, there are no reported studies in the Colombian population.…”
Section: Introductionmentioning
confidence: 99%
“…All mutations found were missense and favour the open con guration of the enzyme allowing its permanent catalytic function [6; 22]. Among the more frequent variants, p.Asn308Asp has been also recorded as the most prevalent in other populations, reaching ~20% in Europe, USA, Argentina [20; 23], Brazil [24] and 11% in South India [11]. It should be noted that intellectual disability of variable degree was negatively associated with PTPN11 mutations compared to other genes tested.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in 1 case who died on scene and was not autopsied, molecular genetics identified a pathogenic variant for a Noonan syndrome due to a mutation in PTPN11. 28 The presence of this syndrome was not known to the family before even though the index patient lost his mother by SUD at young age.…”
Section: Discussionmentioning
confidence: 99%